Strategi Pengembangan Desa Wisata Kawasan Bukit Argo Munung Di Kecamatan Kendal Kabupaten Ngawi - Murti, Endang; Wiyaka, Agus; Iswati, Retno (Universitas Merdeka Madiun, 2019)
Development Strategy for the Bukit Argo Munung Tourism Village in Kendal District, Ngawi District. The tourism potential in each region, including in Ngawi Regency, is an opportunity for increasing tourism both in terms of quantity and quality. Thus, it can maintain the nature of reliability in its contribution to the issue of improvement and the role of tourism in relation to regional development. The research objective was to describe the Development Strategy of the Bukit Argo Munung Tourism Village in Kendal District, Ngawi District. The research findings show that the Tourism Office and Management of the Bukit Argo Munung Region tourist attraction have worked reasonably well in implementing the Tourism Development Strategy in Increasing the Number of Tourists visiting the Bukit Argo Munung Region tourist attraction.